Opportunities and Challenges in Accelerating Renewable Energy Transition: A Case Study of Lhokseumawe, Aceh, Indonesia - Zulhilmi, Zulhilmi; Fahmi, Asrul; Mauludi, Mauludi; Hidayat, Bimby (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
Indonesia faces a growing energy demand amid increasing environmental and economic challenges, particularly due to its continued reliance on fossil fuels. While national policies and international commitments have set ambitious targets for renewable energy adoption, implementation at the local level remains limited. This study aims to explore the opportunities and challenges of accelerating renewable energy transition policies in Lhokseumawe, Aceh, using a qualitative case study approach. Data were collected through semi-structured interviews, field observations, and document analysis involving key stakeholders and local communities. The findings reveal that although Lhokseumawe has substantial renewable energy potential and widespread public utility coverage, local efforts are hampered by insufficient funding, regulatory ambiguities, technical capacity gaps, and deeply rooted traditional practices such as informal oil drilling. Nonetheless, positive developments are observed in the form of local energy planning initiatives, public-private partnerships, and increasing community engagement. This research underscores the need for stronger local government authority, innovative financing, and community empowerment to bridge the gap between national policy ambitions and local realities, providing practical insights for Indonesia’s just and inclusive energy transition.